Multi drug resistant (MDR) tuberculous meningitis with hydrocephalus treated with ventriculo-peritoneal shunting: a review - Gautam, Vinod; Khurana, Sarbjeet; Singh, Ravinder (International Journal of Medicine, 2015)
Introduction: Tubercular meningitis (TBM) is one of the severe manifestations of extra pulmonary tuberculosis. Prognosis of cases of multidrug resistance TBM is even worse. We present report of three cases of MDR tuberculous meningitis with hydrocephalus to highlight the challenges in the management of these patients.Materials and Methods: The present study was done was done at IHBAS, a tertiary care neuropsychiatry hospital in Delhi, India. Three patients of MDR CNS TB treated at neurosurgery department were included in this study. Study design was a descriptive case series.Results: All three cases were treated with second line ATT and ventrriculoperitoneal shunting. After a regular follow up with clinical and neuroimaging vigil and with laboratory testing, these patients showed improvement.Conclusion: The decision to start second line ATT to treat resistant cases of CNS TB is often delayed and increases the morbidity and mortality. Prompt and precise decision is possible with vigilant clinical observation, lab tests and neuroimaging. Close follow-up is mandatory for detecting any adverse drug effect and therapeutic response in patients of MDR-CNS TB.